Reading for life: The Critical Literacy and Literature Project at UNLPam (2013-2016) - Basabe, Enrique Alejandro; Germani, Miriam Patricia (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
During the last year in their ELT programme, students face dilemmas which are more philosophical than linguistic in nature. Literature becomes then a fertile ground for reflective thinking; and critical literacy, a suitable approach to engage in novel ways of reading the world and of appropriating the curriculum. In this classroom account, we offer the preliminary results of a pilot study we carried out in the course on literatures in English we taught at the National University of La Pampa (UNLPam) during the second term of 2013. That action was framed in the research project Critical literacy and literature in English language teacher education, which we devised for 2013-2016 and of which we also offer a brief description.